Choices part II the upward call - Quitain, Bobby (C & E Pub., 2008)
"A life of blessing is just a choice away. Follow Bobby Quitain as he leads you by the hand towards an exciting and fantastic life with God. Defy your past. Defend your present. Define your future. Embrace the "upward call" of God for your life!"--Back cover.